Global burden of cancer attributable to high BMI (1990–2031): a multidimensional analysis based on GBD and Mendelian randomization - Zhu, Xianglin; Mi, Yushuai; Wang, Lang; Liang, Hao; Zhang, Jie; Zhao, Shijun; Zhao, Cheng; Ding, Yinlu (Frontiers in Nutrition, 2025)
ObjectiveObesity-related health burdens have emerged as particularly intractable public health issues on a global scale. This study aims to analyze the association between body mass index (BMI) and 12 types of cancer, examine the regional, gender, and age disparities in cancer burden attributable to high BMI, and project the disease burden trends over the next decade based on available data.MethodsData for this study were sourced from the Integrative Epidemiology Unit (IEU) Open Genome-Wide Association Study (GWAS) Project and the 2021 Global Burden of Disease (GBD) database. Using Mendelian randomization (MR), we investigated the association between BMI and 12 cancer types. We also collected and analyzed epidemiological data on cancers attributable to high BMI, calculated the estimated annual percentage change (EAPC) across 21 regions, and examined disparities in mortality and disability-adjusted life years (DALYs) by age, sex, and cancer type. Finally, we used the autoregressive integrated moving average (ARIMA) model to predict trends in various cancers attributable to high BMI over the next 10 years.ResultsIn 2021, high BMI accounted for 356,738 cancer deaths worldwide and 8,894,525 DALYs, representing an increase of 160% in deaths and 151% in DALYs compared to 1990 (which recorded 137,353 deaths and 3,549,049 DALYs). Among the cancers attributable to high BMI, colon and rectal cancer accounted for the highest disease burden, while thyroid cancer accounted for the lowest proportion of disease burden. Gender-stratified analysis revealed a notably higher disease burden among women compared to men. An age-specific assessment revealed a disproportionately higher disease burden in the 50–79 age cohort. Additionally, both the age-standardized mortality rate (ASMR) and age-standardized disability rate (ASDR) showed positive correlations with the Socio-demographic Index (SDI). Finally, projections from the ARIMA model indicate that over the next decade, the ASMR for most cancers attributable to high-BMI will remain stable or increase, except for colon, rectal, and uterine cancers. The MR analysis indicated a causal relationship between BMI and 11 cancer types (colon and rectal cancer, liver cancer, gallbladder and biliary tract cancer, pancreatic cancer, breast cancer, uterine cancer, ovarian cancer, kidney cancer, lymphoma, multiple myeloma, and leukemia), while no causal association was found between BMI and thyroid cancer.ConclusionMendelian randomization analysis indicated a notable association between elevated BMI and an increased risk of 11 cancer types. Over the past three decades, the cancer burden attributable to high BMI has demonstrated a marked increasing trend, with notable variations observed across geographic regions, gender groups, and age categories regarding predominant cancer types. These findings underscore the need to develop targeted prevention strategies and health promotion interventions that are tailored to specific demographic and regional profiles.